Soekertijo: The Lunge of Officers from Lumajang 1946-1988 - Anggraeni, Dwi Ayu; Suharto, Suharto; Izzah, Latifatul (JURNAL HISTORICA, 2023)
This thesis discusses the role and career of Soekertijo during his time in the military. Soekertijo first entered the world of military education during the Japanese occupation of Indonesia, he graduated from Pembela Tanah Air (PETA). After Indonesia's independence, he formed Section II. Soekertijo Company began to show its work in the national arena such as defending Indonesia's sovereignty from Dutch Military Aggression I and Dutch Military Aggression II, in addition, Soekertijo also cracked down on separatist groups such as DI/TII to PRRI. The approach used by the author is the Biography approach, while the theory used in this study is the Charisma Theory from Max Weber's writings. The writing of this thesis is more emphasized on Soekertijo's role when defending Indonesia's independence, is a history in the form of a biography, because it will narrate the events of Soekertijo's past as part of the process of forming his leadership spirit, adolescence and his journey before becoming a company commander to becoming a Major General. The temporality of this article began in 1946, which was the momentum for the success of Section II of Kompi Soekertijo in defeating the Dutch Military at Klakah Station, while the deadline for this article was 1988, marking the inauguration of the Juang Kompi Soekertijo Monument in Yosowilangun as a form of appreciation for his dedication to country. Keywords: Soekertijo, Section II of the Soekertijo Company, Military, Dutch Military Agression and Separatist Group.